Daily field checking list by Walter Rosene, April 21, 1940 - Rosene, Walter M., Sr., 1880-1941et al; Iowa Ornithologists' Unionet al
Daily field checking list of birds observed at Dunbar Slough by Walter Rosene, Robert Walker, Samuel J. Hyde and Earl Peterson, April 21, 1940. Plustek--flatbed